Digital transformation in supply chains: Assessing the spillover effects on midstream firm innovation - Jiangying Wei; Xiuwu Zhang; Takashi Tamamine (Journal of Innovation & Knowledge (JIK), 2024)
Amidst rapidly evolving market conditions, relying solely on internal information and knowledge for innovation has proven inadequate. The emergence of the digital economy injected renewed vitality into enterprise innovation. However, existing studies have predominantly concentrated on the digital transformation intrinsic to enterprises, neglecting the impact of partners' digital transition on enterprises' innovation performance. From the perspective of supply chain spillovers, this study evaluates the influence of digital transitions in upstream and downstream enterprises on the innovation activities of midstream enterprises. The results show that the digital transformation of enterprises within the supply chain exhibits a transmission effect, and the digital transformation of upstream and downstream enterprises significantly promotes the innovation performance of midstream enterprises. The mechanistic analysis revealed that the digital transformation of upstream and downstream enterprises mainly enhances the resilience of the supply chain by improving its efficiency, optimizing the match between supply and demand, and stabilizing the relationship between supply and demand, thus promoting the innovation level of midstream enterprises. Further analysis shows that improvements in the innovation output of midstream enterprises are reflected in the quality of innovation. When the upstream and downstream firms belong to the same industry, the supply chain spillover effect of digital transformation is more evident, and simultaneously, the digital collaboration of the supply chain can promote the innovation of midstream enterprises.
Keywords: 650; Digital transformation; Enterprise innovation; Supply chain spillover